Salt ratios respond to saline irrigation and sewage sludge application in pearl millet-wheat rotation - ANKUSH, ANKUSH; PRAKASH, RAM; SINGH, RAMESHWAR; KUMARI, SACHIN; LOUHAR, GANPAT (The Indian Journal of Agricultural Sciences, 2021)
Salinity is a limiting factor for crop production in irrigated areas. A field experiment was conducted for two consecutive years (2017-19) using three irrigation treatments, viz. canal water (0.35 dS/m) and saline water (8 and 10 dS/m); and five fertilizer treatments, viz. control, sewage sludge (SS)-5 t/ha, SS (5 t/ha)+50% recommended dose of fertilizers (RDF), SS (5 t/ha)+75% RDF and 100% RDF, to evaluate the effect of saline water irrigation, organic and inorganic fertilization on salt ratios in pearl millet and wheat crops. However, SS was applied in the Rabi only. As the salinity of irrigation water increased, the salt ratios (Na+/K+ and Cl-/SO4 2) in pearl millet and wheat crops were increased markedly during both years. However, SS (5 t/ha) + 75% RDF recorded the lowest Na+/K+ ratio in pearl millet crop over control, but it was statistically at par with 100% RDF, while in wheat crop, the ratio was decreased considerably under 100% RDF treatment followed by sewage sludge amended treatments. Also, the ratio (Cl-/SO4 2-) in both crops was significantly decreased with sewage sludge incorporation, and the lowest was recorded with SS (5 t/ha) + 75% RDF. From the present study, it is concluded that the SS and inorganic fertilizer application helps in gaining potential of cereals against salt stress by reducing Na+ and Cl- besides increasing potassium and sulphate contents in plants.